2012
DOI: 10.1371/journal.pone.0048024
|View full text |Cite
|
Sign up to set email alerts
|

Alteration of Cellular Behavior and Response to PI3K Pathway Inhibition by Culture in 3D Collagen Gels

Abstract: Most investigations into cancer cell drug response are performed with cells cultured on flat (2D) tissue culture plastic. Emerging research has shown that the presence of a three-dimensional (3D) extracellular matrix (ECM) is critical for normal cell behavior including migration, adhesion, signaling, proliferation and apoptosis. In this study we investigate differences between cancer cell signaling in 2D culture and a 3D ECM, employing real-time, live cell tracking to directly observe U2OS human osteosarcoma a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
69
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 78 publications
(82 citation statements)
references
References 54 publications
9
69
0
Order By: Relevance
“…15,89,90 In both the microcavity and the microcapillary designs, it is important that the size of the cavity or capillary match with the size of spheroids, allowing the spheroids to be adequately analyzed by maintaining their shape and properties during measurements. 88 In these designs, Culture condition can be modified to include factors/proteins found in particular tumor microenvironment 17 Heterogeneous cell population are similar to cells of tumor that are in different phases of cell cycle including proliferating, hypoxic, and necrotic cells 24,53 The gene and protein expression levels of cells and thus the cellular behaviors are similar to in vivo levels 17,[27][28][29][30][31]40 Provide in vitro models for including different types of cells to build multicellular systems 52 Bridges the gap between in vitro and in vivo drug screening, possibly decreasing the use of animal models 5 …”
Section: D Cell Cultures In Cell-based Biosensorsmentioning
confidence: 99%
See 1 more Smart Citation
“…15,89,90 In both the microcavity and the microcapillary designs, it is important that the size of the cavity or capillary match with the size of spheroids, allowing the spheroids to be adequately analyzed by maintaining their shape and properties during measurements. 88 In these designs, Culture condition can be modified to include factors/proteins found in particular tumor microenvironment 17 Heterogeneous cell population are similar to cells of tumor that are in different phases of cell cycle including proliferating, hypoxic, and necrotic cells 24,53 The gene and protein expression levels of cells and thus the cellular behaviors are similar to in vivo levels 17,[27][28][29][30][31]40 Provide in vitro models for including different types of cells to build multicellular systems 52 Bridges the gap between in vitro and in vivo drug screening, possibly decreasing the use of animal models 5 …”
Section: D Cell Cultures In Cell-based Biosensorsmentioning
confidence: 99%
“…A variety of cell lines showed reduced proliferation rate in 3D cultures compared to those cultured in 2D. 17,[27][28][29][30][31] 33 But interestingly, the same cell line cultured on the synthetic poly(2-hydroxyethylmethacrylate) (polyHEMA) 3D scaffold, exhibited a proliferation rate that was 7.2-fold slower than in 2D culture, 33 which suggests that the cell proliferation rate is also related to the type of 3D model in which the cells are cultured. In general, the proliferation rate of cells grown in 3D culture better represent the growth of tumors in vivo compared to those cultured in an unnatural 2D environment.…”
mentioning
confidence: 99%
“…These studies have also identified differences in drug sensitivity among cells cultured in 2D compared to 3D systems 5, 9, 10, results of which support the increased use of 3D models for drug evaluation 10, 11.…”
Section: Introductionmentioning
confidence: 66%
“…These experiments attempt to elucidate from statistical results the processes involved in migration, including cell signaling and protein interactions, as well as the effect of exposure to drugs. 17,47 The evidence collected, however, is insufficient to quantify the stem cell migration dynamics even at single cell level due to the complexity of the issues and the diversity of biological mechanisms present in stem cells. Figure 1 shows the abundance of factors accounting for the complexity of the process of stem cell migration; it summarizes schematically the different chemical factors involved in determining cellular behavior and zooms in on the geometrical and mechanical properties that affect migration for ECMcell interactions (Fig.…”
Section: Need For Computational Modeling Of Stem Cell Migrationmentioning
confidence: 99%
“…4,6 Similarly, it has been used to understand phenomena resulting from chemically induced migration, such as haptotaxis 59 and chemotaxis. 17 In this review, we focus on computational modeling of stem cell migration. Efforts modeling of other cell types are shortly outlined and their potential application in the study of stem cells discussed.…”
Section: Introductionmentioning
confidence: 99%